Implementasi Sistem Informasi Berbasis Web Untuk Meningkatkan Efisiensi Operasional Dan Kepuasan Pelanggan - Bagaskara, Pradana Galang; Nindyasari, Ratih; Wijayanti, Esti (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The digital transformation in the food and beverage (F&B) industry has encouraged cafes to adopt technology to enhance operational efficiency and customer satisfaction. Sunday Coffee Kudus faces operational challenges, such as errors in order recording, long queues, and suboptimal management of services. This study aims to design and implement a web-based information system using the CodeIgniter framework with a waterfall development methodology. The system includes a self-ordering feature that allows customers to independently place orders through a user-friendly interface, reducing waiting times and queues. Additionally, the system supports automated transaction recording and efficient customer data management. The implementation results show improved operational efficiency, increased customer satisfaction, and higher order volumes, reflecting the convenience and ease of the service. The system also reduces the workload of cashiers and streamlines operational processes. This study provides significant contributions to the digitalization of the local F&B industry by offering an adaptive and effective technological solution, serving as a strategic step to enhance business competitiveness in the digital era.